Let s praise the courage of the peasant farmer - Saba Gana, Andrew (Technical Centre for Agricultural and Rural Cooperation, 2001)
Let s praise the courage of the peasant farmerFarming is a risky venture, a very risky venture indeed. Unlike almost any other business enterprise, the inputs required for production are subject to natural factors, out of the control of the person...